Esso and the executive search: a research study on the problems of recruiting bumiputra engineers and accountants in Esso / Mohd. Safian Jaafar - Jaafar, Mohd. Safian (1981)
Esso, a part of Exxon, the organization that is a world leader in the effort to seek and develop enough energy to meet Malaysia's present and future needs. Being a contractor to PETRONAS, Malaysia's national oil company, Esso carries out a full programme of exploration and production activities that call for the expertise of innovative and committed professionals.